Corrosion Behavior of Titanium Frameworks under Laser and Tungsten Inert Gas Weldings: Applications in Dentistry - Rodrigues, S. A. (2020)
The purpose of this study was to investigate the role of different welding techniques: laser and tungsten inert gas (TIG) on the corrosion behavior of commercially pure titanium (cp-Ti) frameworks in dentistry. Electrochemical tests were conducted in artificial saliva at pH 7.2, 37 degrees C. The surfaces were examined using scanning electron microscopy. The received data were analyzed by one-way ANOVA followed by Tukey's test for multiple comparisons (alpha = 0.05). Cp-Ti frameworks welded by TIG were found to be more susceptible to corrosion, where defects in the weld region appeared to be the most important factor for the corrosion behavior. These findings suggested a better corrosion behavior for the laser welding procedure.